2020
DOI: 10.21203/rs.3.rs-48785/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GSK3β Inhibition Synergizes with PARP Inhibitors through the Induction of Homologous Recombination Deficiency in Colorectal Cancer

Abstract: Background: Monotherapy with poly ADP-ribose polymerase (PARP) inhibitors results in limited objective response rate (≤ 60% in most cases) in patients with homologous recombination repair (HRR)-deficient cancer, which suggests a high rate of resistance in this subset of patients to PARP inhibitors (PARPi). To overcome resistance to PARPi and to broaden their clinical use, we performed high-throughput screening of 99 anticancer drugs in combination with PARPi to identify potential therapeutic combinations. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…To this end, we performed a two-step screening strategy, comprising a histone-based ELISA assay for the primary hit finding, followed by further assessment of the hit compounds of interest using the DSB FA model. Our screen led to the identification of thioparib as a potential PARP inhibitor, with an IC 50 of 0.13 nM; the structure is shown in Fig 1A (Zhang et al, 2015). We observed an approximately 2-fold difference in potency between thioparib and its enantiomer, entthioparib (Cpd-391; PARP1 IC 50 = 0.26 nM) (Appendix Table S1).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…To this end, we performed a two-step screening strategy, comprising a histone-based ELISA assay for the primary hit finding, followed by further assessment of the hit compounds of interest using the DSB FA model. Our screen led to the identification of thioparib as a potential PARP inhibitor, with an IC 50 of 0.13 nM; the structure is shown in Fig 1A (Zhang et al, 2015). We observed an approximately 2-fold difference in potency between thioparib and its enantiomer, entthioparib (Cpd-391; PARP1 IC 50 = 0.26 nM) (Appendix Table S1).…”
Section: Resultsmentioning
confidence: 93%
“…The compound 4- 6,7,2,4]triazolo [4,3-a]pyrazine-7-carbonyl)benzyl)phthalazin-1(2H)-one (Cpd-391) and (R)-4- (4-fluoro-3-(5-methyl-3-(thiazol-2yl)-5,6,7,8-tetrahydro-[1,2,4]triazolo[4,3-a]pyrazine-7-carbonyl)ben zyl)phthalazin-1(2H)-one (thioparib) were synthesized at the Shanghai Institute of Material Medica at the Chinese Academy of Sciences following a similar procedure as described in the Chinese patent, CN201510818057.7 (Zhang et al, 2015). High-performance liquid chromatography (HPLC) analysis confirmed that the purity of both thioparib and Cpd-391 was ≥ 98%.…”
Section: Synthesis Of Thioparib and Cpd-391mentioning
confidence: 99%